World Federation of Societies of Biological Psychiatry (WFSBP) guidelines for biological treatment of schizophrenia. Part 1: acute treatment (Archives of Clinical Psychiatry, 2006)
These guidelines for the biological treatment of schizophrenia were developed by an international Task Force of the World Federation of Societies of Biological Psychiatry (WFSBP). The goal during the development of these guidelines was to review systematically all available evidence pertaining to the treatment of schizophrenia, and to reach a consensus on a series of practice recommendations that are clinically and scientifically meaningful based on the available evidence. These guidelines are intended for use by all physicians seeing and treating people with schizophrenia. The data used for developing these guidelines have been extracted primarily from various national treatment guidelines and panels for schizophrenia, as well as from meta-analyses, reviews and randomised clinical trials on the efficacy of pharmacological and other biological treatment interventions identified by a search of the MEDLINE database and Cochrane Library. The identified literature was evaluated with respect to the strength of evidence for its efficacy and then categorised into four levels of evidence (A/D). This first part of the guidelines covers disease definition, classification, epidemiology and course of schizophrenia, as well as the management of the acute phase treatment. These guidelines are primarily concerned with the biological treatment (including antipsychotic medication, other pharmacological treatment options, electroconvulsive therapy, adjunctive and novel therapeutic strategies) of adults suffering from schizophrenia.